A study of different routes of hysterectomies and its outcome in benign gynaecological conditions in tertiary care centre in Tamil Nadu - Arumugam, Kiruthika; Rajakumar, Shery A.; Kumar, Janarthanan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Hysterectomy is the most frequently performed major surgical procedure in gynaecology. It is an efficacious treatment option for numerous gynaecological conditions. This study aimed to investigate the different routes of hysterectomies, such as abdominal, vaginal, and laparoscopic, and their outcomes in benign gynaecological diseases in a tertiary care centre in Tamil Nadu. Methods: This retrospective observational study included 200 patients who were admitted to the department of obstetrics and gynaecology at Chettinad Hospital and Research Institute, Tamil Nadu, India underwent hysterectomy between January 2021 and January 2023, and were collected from the MRD. Patient history included age, parity, indication for surgery, duration of surgery, route of hysterectomy, intraoperative or postoperative complications, duration of hospital stay were collected. Results: This study analysed 200 patients who underwent hysterectomy, with the majority aged between 40-50 years (60%) and multiparous women (85%). The most common indications were abnormal uterine bleeding (80%), uterine prolapse (12%), benign ovarian cyst (5%) and post-menopausal bleeding (3%). Total abdominal hysterectomy (49%) was the most common approach, followed by vaginal/non-descent hysterectomy (19.5%), total laparoscopic hysterectomy (16.5%), and laparoscopic-assisted vaginal hysterectomy (15%). Complications included wound infections (3.5%), excessive bleeding (3%), bladder injuries (1%) and ureter injury (0.5%). The procedure duration and hospital stay were shorter for vaginal and laparoscopic approaches than for open abdominal hysterectomy. The laparoscopic approach had the lowest rates of complications such as bladder injuries and excessive bleeding. Conclusions: Vaginal hysterectomy is preferred for uterine prolapse, whereas laparoscopic techniques offer benefits such as reduced blood loss and lesser hospital stay and morbidities. Although rare, complications emphasize the need for careful postoperative monitoring to optimize patient care.